Phenomenon of Sediment Distribution Patterns in Bends Due to Changes in Check Dam Layout - Nurul Kurniasari; Darwizal Daoed; Nurhamidah (CIVED, 2025)
Indonesia has high rainfall, which often causes flooding. Large volumes of rainwater cause sediment in river channels to move from upstream to downstream. The shape of rivers in Indonesia tends to bend, so the researcher conducted a study of the turning channel using a check dam structure with three placement conditions, namely before the bend, in the middle of the bend, and after the bend. This research was conducted at the Fluid Mechanics and Hydraulics Laboratory, Department of Civil Engineering, Faculty of Engineering, Universitas Andalas, Padang. This study aims to determine the impact of sediment on erosion caused by the placement of check dams on river bends and to determine the distribution of sediment due to changes in the position of Check Dam buildings on river bends. A 12.8 m long channel, made of 5 mm acrylic, with a cross section of 0.4 m x 0.4 m and a bend angle of 120o, was used in the experiment. Researchers measured flood discharge and sediment distribution for each of the three check dam positions. The study showed that the sediment distribution varied significantly depending on the location of the check dam. The researchers observed that the most balanced sediment distribution, with relatively equal deposition on the inner and outer sides of the bend, occurred when the check dam was placed after the bend. Based on these findings, they recommend placing check dams after bends in meandering rivers to minimize erosion and promote a more balanced sediment distribution.